Pressure Effectiveness At The GB-21 Acupressure Point On ASI Production In Post Sectio Caesarea) - Putri Permata; Irna Irna Nursanti; Giri Widakdo (JURNAL KEPERAWATAN CIKINI, 2021)
Breast milk production is influenced by the secretion of the hormones prolactin and oxytocin. Caesarean section delivery is at risk of delaying exclusive breastfeeding because post-caesarean section mothers still focus on pain and are influenced by drugs during surgery so as to overcome the problem, Pressure at Acupressure Points Gb-21 is applied. Quasi experimental research method with one group pre-post test design. The sample of this research was 17 women from Post Sectio Caesarea. Results Pressure at the acupressure point Gb-21 is more effective for increasing milk production in post-sectio caesarean mothers than the indicators of the mother, the result is p value = 0.000 and the baby indicator pressure at the acupressure point GB-21 is also effective for increasing milk production in post-sectio mothers. caesarea, with the resulting p value = 0.000. Pressure intervention at the Gb-21 acupressure point is effective in promoting milk production, relaxing and helping to improve breast blood circulation. Further research needs to be done to add new variables related to nonpharmacological pressure therapy at the acupressure point Gb-21.